The old man and the sea - Hemingway, Ernest, 1899-1961. (New York : London : Scribner, Arrow Books, 2004)
Story of an old fisherman's struggle against natural obstacles that hinder the catch of a huge marlin.
Keywords: Fishers -- Fiction; Older men -- Fiction; Male friendship -- Fiction; Cuba -- Fiction; Bildungsromane; Allegories